Antibacterial activity of ethyl acetate fraction from methanolic extracts of ant-plant tubers towards Streptococcus sanguis ATCC 10566 - Fatriadi, Fajar; Kurnia, Dikdik; Satari, Mieke Hemiawati (Universitas Padjadjaran, 2018)
Introduction: Streptococcus sanguis is an initial cause of dental plaque formation which is the initial cause of caries. One of the preventive treatments can be done by using the mouthwash containing antibacterial substances. Along time, natural remedies are proven to be having more antibacterial properties. Ant-plant (Myrmecodia pendens Merr. & Perry) tubers are types of epiphytic plant that grows in many parts of Papua, with many health benefits, and are known to contain flavonoids, tannins, and tocopherols. This study was aimed to determine the antibacterial activity of ethyl acetate fraction from methanolic extracts of ant-plant tubers on the growth of Streptococcus sanguis ATCC 10566. Methods: The ant-plant tubers were extracted with soxhletation method using the methanol solvent. The fractionation was then performed using ethyl acetate to obtain the ethyl acetate fraction. Result: The phytochemical test showed that the ethyl acetate fraction of the ant-plant contained phenolics, tannins, flavonoids, and terpenoids. The bacterial test in this study was using the microdilution method using the ELISA Reader by measuring the Minimum Inhibitory Concentration (MIC) of ethyl acetate fraction of ant-plant tubers towards Streptococcus sanguis with positive control was using the chlorhexidine gluconate as the golden standard medication. The ethyl acetate fraction of ant-plant tuber had an antibacterial effect towards Streptococcus sanguis in the MIC of 31.25 ppm, while chlorhexidine gluconate was 0.49 ppm. Conclusion: The ethyl acetate fraction of ant-plant had a lower antibacterial activity compared to chlorhexidine gluconate on the growth of Streptococcus sanguis ATCC 10566.Keywords: Ant-plant tubers, Myrmecodia pendens Merr. & Perry, antibacterial activity, Streptococcus sanguis ATCC 10566.